Accelerometer measured physical activity patterns of children during segmented school day in Abu Dhabi - Rahma Ajja; Ludmilla F. Wikkeling-Scott; Keith Brazendale; Rafiq Hijazi; Abdishakur Abdulle (BMC, 2021)
Abstract Background The overwhelming majority of United Arab Emirates (UAE) school-aged children do not meet the 60 min per day recommendation of moderate-to-vigorous physical activity (MVPA). Understanding the different school day segments contribution to children reaching this goal is a crucial step toward developing successful strategies to promote school day MVPA levels. This study aimed to objectively measure children's' physical activity levels and to examine the difference in physical activity levels between high active and low active children during the school day in Abu Dhabi. Methods A total of 133 school children (56% boys; mean age 10.5 years; grades 4-7) from two elementary schools in Abu Dhabi wore accelerometers (ActiGraph GT9X Link) for up to 5 non-consecutive days during spring 2019. Children's' MVPA was estimated during the following school segments: class time, lunch, recess, physical education (PE), and whole school day. Children were stratified as "high active" meeting the ≥30 min/day MVPA school time guideline or "low active" accumulating < 30 min/day MVPA. Results On average children accumulated 21.8 ± 22.6 min/day of MVPA on PE days and 22.4 ± 15.9 min/day of MVPA on non-PE days. Only 19% of children met the 30 min or more of school day MVPA recommendation, with higher proportion of boys (27%) meeting such recommendation compared to girls (8%). High active boys, spent the highest percent of time in MVPA during PE (28%), followed closely by lunch (27%). In compression, high active girls spent the highest percent of time in MVPA during lunch (14.2%) followed by recess (9.1%). High active children accumulated 15.06 more minutes of MVPA during PE (p < 0.001), 2 more minutes during recess (p < 0.001), 3 more minutes of MVPA during lunch (p < 0.001) and 5 more minutes of MVPA during class time (p < 0.001). Conclusion The overwhelming majority of school children did not meet the recommended 30 min /day MVPA during school time. Girls substantially accumulated less MVPA and more sedentary minutes across all segments during the school days compared to boys. Further research is needed to investigate school day segments contribution to children MVPA in the UAE.